ECOLOGY AND PARASITOLOGICAL ANALYSIS OF HORSE FLIES (DIPTERA: TABANIDAE) IN ANTIOQUIA, COLOMBIA - PARRA-HENAO GABRIEL; ALARCÓN-PINEDA ERIKA PATRICIA; LÓPEZ-VALENCIA GUSTAVO (Caldasia)
During the months of June to September 2006, collections of tabanids (Diptera: Tabanidae) and ticks were conducted in the Caucasia municipality, Antioquia, Colombia. Tabanids were caught on horses during daylight using hand nets and pots at the ecotone zone between secondary forests and paddock habitats. Ticks were collected directly from cattle by hand. The purpose of the study was to identify possible vectors of bovine trypanosomosis, and register the diversity and abundance of tabanids in the zone. The arthropods were brought to the laboratory for taxonomic determination and protozooans searching in proboscis, midgut, and salivary glands of flies. In the case of ticks, protozoans were searched in hemolymph. One hundred and forty tabanids belonging to four genera and nine species were caught. Among the species, Lepiselaga crassipes was the most abundant (43.6%), with the highest abundance in July and a biting peak at 14:00 h. The highest diversity of tabanids was observed during September. Three tabanids were found infected with flagellates morphologically compatible with Trypanosoma vivax. 315 ticks belonging to Boophilus microplus species were collected, all of them negative to flagellates. These results suggest T. vivax transmission by tabanids in the study area. However, the specific status of the parasites should be determined by molecular techniques and the transmission mechanism should be established too by controlled studies